2015
DOI: 10.1108/ijebr-02-2014-0021
|View full text |Cite
|
Sign up to set email alerts
|

A review of research methods in entrepreneurship 1985-2013

Abstract: Findings: The data demonstrate that entrepreneurship research is dominated by positivist approaches and data gathering methods, but that this picture is changing over time. The data also reveal differences in methods used in research published in North American and European journals. Research implications:It is argued that increased discussion of the limitations, benefits and implications of research methods is needed across the field as a whole. It is concluded that although there is some methodological refle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
73
0
7

Year Published

2015
2015
2022
2022

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 112 publications
(90 citation statements)
references
References 80 publications
(203 reference statements)
0
73
0
7
Order By: Relevance
“…; see also McDonald et al. (forthcoming), we had identified the methods used by papers published in five top ranked general entrepreneurship journals from the United States and Europe over a 20‐year period (1985–2004). These journals, which were selected for the previous study in order to represent global scholarship in the field were: Entrepreneurship and Regional Development , Entrepreneurship Theory and Practice , the International Small Business Journal , the Journal of Business Venturing , and the Journal of Small Business Management .…”
Section: Methodsmentioning
confidence: 99%
“…; see also McDonald et al. (forthcoming), we had identified the methods used by papers published in five top ranked general entrepreneurship journals from the United States and Europe over a 20‐year period (1985–2004). These journals, which were selected for the previous study in order to represent global scholarship in the field were: Entrepreneurship and Regional Development , Entrepreneurship Theory and Practice , the International Small Business Journal , the Journal of Business Venturing , and the Journal of Small Business Management .…”
Section: Methodsmentioning
confidence: 99%
“…This analysis would help us reflect on the progress of the field and act as a potential source of published research reviews on women entrepreneurship. McDonald et al (2015) reviewed the research methods used in entrepreneurship from the year 1985 to 2013 and identified six top entrepreneurship journals. These include three top US journals (Journal of Business Venturing, Entrepreneurship: Theory and Practice, and Journal of Small Business Management) and two top European journals (International Small Business Journal, and Entrepreneurship and Regional Development) having impact factors ranging from 1.33 to 2.97.…”
Section: Review Methodsmentioning
confidence: 99%
“…Such approaches run the risk of privileging and reinforcing existing conceptions regarding which growth factors are causally significant. One outcome of this is that growth is frequently explained through reference to a relatively small range of variables, often related to business characteristics, the owner and the external environment (Parry, 2010;Crook et al, 2010;McDonald et al, 2015).…”
Section: Literature Reviewmentioning
confidence: 99%